2010
DOI: 10.1111/j.1399-5618.2010.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Antithetical asymmetry in schizophrenia and bipolar affective disorder: a line bisection study

Abstract: Study findings suggest attenuation of normal pseudoneglect in schizophrenia and accentuation of normal pseudoneglect in BPAD, indicating lesser lateralization in schizophrenia and possibly greater lateralization in BPAD. From an evolutionary perspective, schizophrenia and BPAD might have antithetical origins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 61 publications
4
20
0
Order By: Relevance
“…Barta et al [47] observed that PS deviated further to the right with respect to the control group when they (1) bisected lines placed on the right side of the page and (2) when they used the right hand and the direction of scanning was from right to left. The presence of a rightward bias was subsequently confirmed by Rao et al [48] and Benson and Park [49]. Also in the study by Rao et al [48] participants used the left or right hand.…”
Section: Rightward Bisection Bias Left Hemineglectsupporting
confidence: 51%
See 3 more Smart Citations
“…Barta et al [47] observed that PS deviated further to the right with respect to the control group when they (1) bisected lines placed on the right side of the page and (2) when they used the right hand and the direction of scanning was from right to left. The presence of a rightward bias was subsequently confirmed by Rao et al [48] and Benson and Park [49]. Also in the study by Rao et al [48] participants used the left or right hand.…”
Section: Rightward Bisection Bias Left Hemineglectsupporting
confidence: 51%
“…The presence of a rightward bias was subsequently confirmed by Rao et al [48] and Benson and Park [49]. Also in the study by Rao et al [48] participants used the left or right hand. Authors [48] found that when PS used the right (dominant) hand, they consistently deviated to right.…”
Section: Rightward Bisection Bias Left Hemineglectsupporting
confidence: 51%
See 2 more Smart Citations
“…Up to now, only one recent study has investigated visuospatial attention in BD (psychotic and non-psychotic) and healthy controls by applying a visual line-bisection task (Rao et al, 2010). This study revealed a leftward bias in both psychotic and non-psychotic BD patients compared to healthy controls when using the right hand.…”
Section: Introductionmentioning
confidence: 90%